Multi-drug-loaded gastric-floating microcapsules - Wee, Peixin. (2013)
In this project, we report an advanced gastroretentive polymeric floating microcapsule that simultaneously entraps and releases multiple drugs in a controlled manner, which will reduce patients’ dosing frequency and pill burden. The microcapsule was fabricated using a modified emulsion solvent evaporation method which encapsulated free drug and drug-loaded polymeric particles within the cavity of the hollow carrier. The detail fabrication criteria for the encapsulation of the particles and the formation of microcapsule with a single hollow cavity were identified. The buoyancy of the floating device was also investigated by manipulating the olive oil inclusion in shell matrix, microcapsule size, and microcapsule internal structure. Preliminary study with microcapsule containing two drugs showed sustained drug release in simulated gastric fluid. The study was continued with microcapsule containing three drugs and microcapsule shells with different polymers, such as PLGA, PLLA, and PLLA-PCL blend. The PLLA-PCL composite shell microcapsule provided the most optimized sustained release for hydrophilic, amphiphilic and hydrophobic drugs. To further simulate the human gastrointestinal tract, the release study was also done in gastric fluid, followed by intestinal fluid.